Effectiveness of Discovery Learning Assisted by Chemical Monopoly on Critical Thinking and Learning Outcomes - Martanisa, Mutiah; Hastuti, Budi; Setyowati, Widiastuti Agustina Eko; Kamari, Azlan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
The purpose of this research is to determine the effect of the discovery learning model using chemistry monopoly media on the critical thinking skills and learning outcomes of 11th-grade students. This research employs a quantitative descriptive approach with a quasi-experimental design and a pretest-posttest nonequivalent control group design, utilizing instruments in the form of tests and an observation guide. The sampling technique used is cluster random sampling. Both the experimental class and the control class have 35 students. This study collected data through tests (pretest and posttest). Data analysis was conducted using normality and homogeneity tests, followed by the Mann-Whitney U test (since the data are not normally distributed), and the N-Gain test for assessing learning effectiveness. The research results indicate that the experimental class achieved a 58.79% increase in learning outcomes, whereas the control class experienced a 36.51% increase. In terms of critical thinking ability, the experimental class showed an improvement of 56.00%, while the control class improved by 37.18%. The Mann-Whitney U hypothesis test revealed the significance of cognitive learning outcomes to be 0.041 and the significance of critical thinking ability to be 0.019. Thus, the implementation of discovery learning affects students' critical thinking skills and learning outcomes in the context of acid-base chemistry